Notes on being a man - Galloway, Scott, 1964- (Simon & Schuster, 2025)
"Boys and men are in crisis. Rarely has a cohort fallen further and faster than young men living in Western democracies. Boys are less likely to graduate from high school or college than girls. One in seven men reports having no friends, and men account for three of every four deaths of despair in America. Even worse, the lack of attention to these problems has created a void filled by voices espousing misogyny, the demonization of others, and a toxic vision of masculinity. But this is not just a male issue: women and children can't flourish if men aren't doing well. As we know from spasms of violence, there is nothing more dangerous than a lonely, broke young man. Scott Galloway has been sounding the alarm on this issue for years. In Notes on Being a Man, Galloway explores what it means to be a man in modern America. He promotes the importance of healthy masculinity and mental strength. He shares his own story from boyhood to manhood. He explores his parent's difficult divorce, working through his anger and depression issues, trying to make money, and raising two boys. He shares the sometimes funny, often painful, lessons he learned along the way"--